Organizational impacts of the electronic processing system of the Brazilian Superior Court of Justice - Freitas, Christiana Soares de (2015)
This paper presents a study on the social and organizational impacts of the Electronic Processing System (EPS) implemented in 2008 by the Brazilian Superior Court of Justice (SCJ). This system is part of a wider transformation process involving the implementation of a new management model at the SCJ. The theoretical framework of the research conducted is based on the Technology Enactment Theory and other studies on the role of technological innovations in public organizations (Fountain, 2005; Freitas, 2012). Its main goal was to identify the most significant factors facilitating or inhibiting the innovation adoption. Results show different impacts of the EPS on professional groups and organizations. Political, cultural and economic aspects influence stakeholders’ perceptions of the innovation, including its sustainability, time and cost saving that impact the rate of adoption and the realization of benefits both to users and the organization investing in its development.